The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5578/tt.10782
|View full text |Cite
|
Sign up to set email alerts
|

Fatal swine influenza A H1N1 and Mycoplasma pneumoniae coinfection in a child

Abstract: SUMMARY Fatal swine influenza A H1N1 and Mycoplasma pneumoniae coinfection in a child One of the most common causes of death in influenza patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In our study, the ratio of coinfection with multiple pathogens in MP-positive cases was 56.63%, which was higher than previous reports. In MP-positive cases, the co-infection rate with IFV was highest among all cases (24.1%) and this was consistent with the findings of Zheng, et al [27] and Kalenahalli, et al [28]. It has been reported that viral infection can make patients susceptible to MP infection, and that this interaction may lead to the aggravation of asthma [29].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the ratio of coinfection with multiple pathogens in MP-positive cases was 56.63%, which was higher than previous reports. In MP-positive cases, the co-infection rate with IFV was highest among all cases (24.1%) and this was consistent with the findings of Zheng, et al [27] and Kalenahalli, et al [28]. It has been reported that viral infection can make patients susceptible to MP infection, and that this interaction may lead to the aggravation of asthma [29].…”
Section: Discussionsupporting
confidence: 89%
“…As confirmed in previous studies, Streptococcus pneumoniae and Haemophilus influenza are main upper respiratory pathogens in children[4], and both increase almost from September to next March. The change trend may be affected by the flu season[4,5]. It has been reported that influenza virus is interacted with pathogenic bacteria, and confirmed the relation of influenza with Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenza, Neisseria meningitidis, respiratory syncytial virus (RSV), human rhinoviruses, and human parainfluenza viruses, etc [4,6]…”
mentioning
confidence: 79%
“…In humans, Streptococcus pneumoniae , Staphylococcus aureus and Haemophilus influenzae are the three most frequently reported bacteria secondary to influenza infection. Other less common bacteria include Nocardia [25], Mycoplasma pneumoniae [26], Mycobacterium tuberculosis [27], Legionella pneumophila [28], and Campylobacter jejuni [29] . Choi et al performed a retrospective analysis of 636 swine influenza virus (SIV) cases in pigs and found that Pasteurella multocida and Mycoplasma hyopneumoniae were the most common bacteria associated with SIV [30].…”
Section: Discussionmentioning
confidence: 99%